Sphingolipid imbalance and inflammatory effects induced by uremic toxins in heart and kidney cells are reversed by dihydroceramide desaturase 1 inhibition. (10th October 2021) - Savira, Feby; Magaye, Ruth; Scullino, Carmen V.; Flynn, Bernard L.; Pitson, Stuart M.; Anderson, Dovile; Creek, Darren J.; Hua, Yue; Xiong, Xin; Huang, Li; Liew, Danny; Reid, Christopher; et al.
Highlights: Des1 inhibition attenuated cardiac myocytes hypertrophy induced by the protein-bound uremic toxins, indoxyl sulfate and p-cresol sulfate. Des1 inhibition attenuated cardiac fibroblasts and renal mesangial cells collagen synthesis induced by indoxyl sulfate and p-cresol sulfate. PBUTs mediates sphingolipid imbalance & inflammatory responses in heart and kidney cells, and these effects were attenuated by Des1 inhibition. Sphingolipid modifying agents may have therapeutic potential for the treatment of CVD and CKD and warrant further investigation. Abstract: Non-dialysable protein-bound uremic toxins (PBUTs) contribute to the development of cardiovascular disease (CVD) in chronic kidney disease (CKD) and vice versa . PBUTs have been shown to alter sphingolipid imbalance. Dihydroceramide desaturase 1 (Des1) is an important gatekeeper enzyme which controls the non-reversible conversion of sphingolipids, dihydroceramide, into ceramide. The present study assessed the effect of Des1 inhibition on PBUT-induced cardiac and renal effects in vitro, using a selective Des1 inhibitor (CIN038). Des1 inhibition attenuated hypertrophy in neonatal rat cardiac myocytes and collagen synthesis in neonatal rat cardiac fibroblasts and renal mesangial cells induced by the PBUTs, indoxyl sulfate and p-cresol sulfate. This is at least attributable to modulation of NF-κB signalling and reductions in β-MHC, Collagen I and TNF-α gene expression. Lipidomic analyses revealed Des1 inhibition restored C16-dihydroceramide levels reduced by indoxyl sulfate. In conclusion, PBUTs play a critical role in mediating sphingolipid imbalance and inflammatory responses in heart and kidney cells, and these effects were attenuated by Des1 inhibition. Therefore, sphingolipid modifying agents may have therapeutic potential for the treatment of CVD and CKD and warrant further investigation.